The Relationship Between Dietary Patterns and the Incidence of Stunting in Children Aged 24-60 Months in the Sidomulyo Community Health Center Work Area - Wiwi Sartika; Adek Diah Lestari; Sara Herlina (Jurnal Kesmas Prima Indonesia, 2026)
Stunting remains a major global health issue, with 148.1 million children under five affected worldwide (WHO, 2022). Indonesia ranks 21st globally and 4th in Asia, with a national prevalence of 21.5% in 2023 and 13.6% in Riau Province. This condition highlights the importance of examining dietary patterns as a key factor associated with stunting. Objective: To analyze the relationship between dietary patterns and stunting among children aged 24–60 months in the working area of ​​Sidomulyo Public Health Center. Methods: This quantitative study used a cross-sectional design. The population included all children aged 24–60 months, with 57 respondents selected through total sampling from June 24 to July 12, 2025. Data were collected using a validated and reliable questionnaire, and analyzed using Chi-Square tests. Results: The analysis showed a significant association between dietary patterns and stunting (p=0.000; OR=19.200). Children with good dietary patterns were 19 times more likely to achieve normal nutritional status compared to those with poor dietary patterns. Conclusion: Dietary patterns have a significant relationship with stunting among children aged 24–60 months in Sidomulyo, emphasizing the importance of balanced nutrition to prevent stunting.